PENGEMBANGAN MEDIA GAME EDUKASI BERBASIS APLIKASI LECTORA INSPIRE PADA PEMBELAJARAN AKUNTANSI SEBAGAI UPAYA MENINGKATKAN BELAJAR MANDIRI SISWA SMK - Shelviyani, Dea Vitta; Santoso, Sigit; Muchsini, Binti (FKIP Universitas Sebelas Maret, 2017)
ABSTRACTThe Purposes of this research are: (1) providimg a decent of the game education media based on lectora inspire application; and (2) investigate the effectiveness of the game education media based on lectora inspire application in accounting learning as an effort to improve self-directed learning students of vocational high school. The methods of this research are research and development method. Its samples were students in grade X Accounting A and grade X Accounting B as control class and experimental class by random sampling technique. Procedure of the developing game education media based on lectora in-spire application referred to the one claimed by Borg and Gall with some modification. Data of the re-search were collected through questionnaire, feasibility sheet and response sheet.. they were validated by using content validition and construct validition. And analyzed by using the statistical descriptive analysis to investigate the level of self-directed learning and the game education media feasibility, followed with the statistic inferential analysis to investigate the effectiveness of the game education media. The result of the research shows that game education media based on lectora inspire application is feasible to be used base on validation of a media expert (97,4%), a material expert (89,8%), a practitioner (83,8%), and stu-dent assessment (91,6% ) Which are categorized as